2013
DOI: 10.1111/cod.12130
|View full text |Cite
|
Sign up to set email alerts
|

Cost and quality of life in patients with severe chronic hand eczema refractory to standard therapy with topical potent corticosteroids

Abstract: Wellbeing and loss of productivity are the most important consequences in these patients. Appropriate treatment is necessary to improve patient health and productivity, which will contribute to reducing societal costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 33 publications
(67 reference statements)
2
42
0
Order By: Relevance
“…In agreement with a previous study showing that, in patients with HE, widespread eczema was a risk factor for a poor prognosis, an association of eczema on the wrists or feet with high PGA scores during the follow‐up of 2 years was noted. HE has been shown to have a strong impact on QoL . Interestingly, changes in HE severity and QoL are closely linked.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with a previous study showing that, in patients with HE, widespread eczema was a risk factor for a poor prognosis, an association of eczema on the wrists or feet with high PGA scores during the follow‐up of 2 years was noted. HE has been shown to have a strong impact on QoL . Interestingly, changes in HE severity and QoL are closely linked.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that > 60% of patients with severe chronic hand eczema were refractory to standard therapy, around 11·0% of all patients with hand eczema. This result shows the relatively high presence of patients – of those with hand eczema accessing the dermatological reference centres to receive medical assistance – having a condition that is difficult to manage and related to severe impairment of quality of life, and high direct and indirect costs …”
Section: Discussionmentioning
confidence: 97%
“…Severe CHE (sCHE) may interfere with patients' daily activities and the long-term prognosis is poor (2,7,8). CHE has a significant negative impact on patient-reported quality of life, work productivity and daily functioning (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…CHE has a significant negative impact on patient-reported quality of life, work productivity and daily functioning (7)(8)(9)(10)(11). The impact of CHE on work life may vary depending on the nature of the patient's occupation (9,12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation